Association between glucose-to-lymphocyte ratio and long-term mortality among women after coronary artery bypass grafting: filling gaps in female - Kai Zhang; Rong Zhang; Maoxun Huang; Bo Li (BMC Cardiovascular Disorders)
Abstract Background Inflammation plays a pivotal role in the progression of coronary artery disease and increases the risk of mortality in patients undergoing coronary artery bypass grafting (CABG). The glucose-to-lymphocyte ratio (GLR), calculated from serum glucose levels and peripheral lymphocyte counts, is a novel marker of inflammation, but its relationship with outcomes after CABG remains unexplored. The aim of this study was to evaluate the association between GLR and long-term mortality. Methods This retrospective cohort study used data from the Medical Information Mart for Intensive Care (MIMIC) database to examine baseline and outcome data for CABG patients. Participants were stratified into quartiles based on GLR levels, and the Cox proportional hazards model and restricted cubic spline analysis were used to evaluate the association between GLR and mortality. Results A total of 592 adult patients (mean age 70.0 ± 10.3 years, mean BMI 30.6 ± 6.8 kg/m2) were included. After multivariable adjustment, patients in the highest quartile of GLR had a hazard ratio (HR) of 3.3 (95% CI: 1.04–10.49; Q4 vs. Q2), while those in the lowest quartile had a HR of 5.62 (95% CI: 1.71–18.48; Q1 vs. Q2). A U-shaped relationship was observed between GLR and risk of death (P for nonlinearity < 0.05), with sensitivity and subgroup analyses supporting these findings. Conclusions GLR was significantly associated with an increased risk of long-term mortality, with both the highest and lowest quartiles demonstrating elevated hazard ratios compared to the second quartile. Assessing GLR may have clinical relevance for predicting mortality risk, providing valuable insights for preventive strategies and patient management.